Techniques to Reduce Iatrogenic Nasal Seeding in Endoscopic Endonasal Surgery for Skull Base Chordoma - Gersey, Zachary C.; Plute, Tritan; Gupta, Prakash; Fernandes Cabral, David T.; Abou-Al-Shaar, Hussam; Abdallah, Hussein; Muthiah, Nallammai; Wang, Eric W.; Snyderman, Carl H.; Zenonos, Georgios A.; Gardner, Paul A. (Journal of Neurological Surgery Part B: Skull Base, 2025)
Iatrogenic tumor seeding after open and endoscopic endonasal approaches (EEAs) for skull base chordoma are well-described; however, strategies that specifically help to minimize or eliminate seeding in EEAs have not been described.The authors conducted a retrospective review of their experience with EEAs for clival chordomas in the past 20 years, with emphasis on recurrence attributable to iatrogenic seeding. Patterns and factors of seeding are reported and analyzed, and the impact of intraoperative techniques is evaluated for their impact on prevention.About 271 EEAs were performed for 194 patients presenting with clival chordoma at the authors' institution between 2001 and 2020. A total of three cases of iatrogenic seeding (incidence 1.1%) were identified, two from primary tumors and one recurrent. The average time to seeding diagnosis was 32.7 months. Beginning in August 2014, an Endonasal Access Guide (nasal sleeve) was used (34.1% of all endonasal cases), and in June 2019, a side-cutting aspirator (used in 4.1% of total cases) was used. There were no incidences of seeding in patients operated on with either side-cutting aspirator or the nasal sleeve (mean follow-up 51.9 months), which was a significant decrease (p < 0.001).Nasal seeding is a rare but potentially preventable complication in endoscopic endonasal surgery for skull base chordoma. Recognition of this entity, deployment of novel surgical tools, and use of meticulous surgical technique should be utilized to minimize surgical seeding in EEA.
Keywords: EEA; skull base; operative technique; chordoma; tumor seeding; minimally invasive